New Roles for EVs, miRNA and lncRNA in Bovine Embryo Implantation - Imakawa, Kazuhiko; Matsuno, Yuta; Fujiwara, Hiroshi (Frontiers in Veterinary Science, 2022)
The sine qua non of new life is fertilization. However, approximately 50% of fertilized eggs/blastocysts in cattle and up to 75% of those from human assisted reproductive procedures fail during the first 3 to 4 weeks of pregnancy, including peri-implantation periods. In these periods, blastocyst hatching and implantation to the maternal endometrium proceeds, during which physiological events such as epithelial-mesenchymal transition (EMT) and trophoblast cell fusion occur. Quite recently, extracellular vesicles (EVs) with micro RNAs (miRNAs) and long non-coding RNAs (lncRNAs) have been found to play a pivotal role for the establishment of the proper uterine environment required for peri-implantation processes to proceed. New findings of EVs, miRNA, and lncRNAs will be described and discussed to elucidate their connections with conceptus implantation to the maternal endometrium.